Denver's Citizen/Police Complaint Mediation Program: Officer and Complainant Satisfaction. (September 2013) - Schaible, Lonnie M.; Angelis, Joseph De; Wolf, Brian; Rosenthal, Richard
Ensuring police use their authority justly is a persistent concern. Yet, there is little agreement on the most effective mechanisms for promoting accountability. The present study seeks to contribute to a growing body of research on mediation of police disputes by assessing variation in levels of satisfaction among officers and citizens. Using data collected by the Denver Office of the Independent Monitor, the study assesses the degree to which mediation produced differential levels of satisfaction. The study finds that both police and civilian participants in the mediation program were significantly more satisfied than individuals who participated in traditional complaint processing. In addition, the study finds that mediation is likely to have even stronger effects on satisfaction for Latino complainants, and female police officers. Implications and suggestions for future research are discussed.